2019
DOI: 10.1039/c9ra01379b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene oxide/poly(vinyl alcohol) composite membrane and pervaporation performance for ethanol dehydration

Abstract: The separation factor of the composite GOP-2.0 membranes could reach 3 059, which is 16 times higher than PVA membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
2
26
1
Order By: Relevance
“…The values of the total mass flux through the membranes are shown in Figure 3. Our values (0.25-1.8 kg m −2 h −1 ) are significantly higher than those reported, for instance, by Hua et al [31] (0.2-0.4 kg m −2 h −1 ) and Cheng et al [48] (0.1-0.45 kg m −2 h −1 ). In fact, only two of the 16 values of flux in Figure 3 are less than 0.45 kg m −2 h −1 .…”
Section: Ethanol-water Mixturescontrasting
confidence: 76%
“…The values of the total mass flux through the membranes are shown in Figure 3. Our values (0.25-1.8 kg m −2 h −1 ) are significantly higher than those reported, for instance, by Hua et al [31] (0.2-0.4 kg m −2 h −1 ) and Cheng et al [48] (0.1-0.45 kg m −2 h −1 ). In fact, only two of the 16 values of flux in Figure 3 are less than 0.45 kg m −2 h −1 .…”
Section: Ethanol-water Mixturescontrasting
confidence: 76%
“…The materials must encompass properties such as film-forming ability, high selectivity, higher permeation flux, good mechanical strength, and good shelf life. Research in this direction has shown that hydrophilic materials are always suitable for the dehydration of alcohols, and many such membrane materials have been studied for dehydration of alcohols [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On increasing the temperature, the increased free volume in the membrane resulted in the permeation of both components across the membrane; therefore, the ux increased and the separation factor decreased. 34,42 The temperature dependence of ux can be expressed by the Arrhenius-type relationship show in eqn (5). 39,43…”
Section: Effect Of Operating Conditionsmentioning
confidence: 99%